2021
DOI: 10.1055/s-0040-1722201
|View full text |Cite
|
Sign up to set email alerts
|

Neuroma Prevention and Implantation Effects of NEUROCAP in Rat Sciatic Nerve Model

Abstract: Introduction Symptomatic neuroma with neuropathic pain can develop following peripheral nerve injury. Current interventions for symptomatic neuroma have unpredictable results. NEUROCAP (Polyganics, Groningen, The Netherlands) is a bioresorbable nerve capping device intended to protect a peripheral nerve end and separate the nerve from the surrounding environment, to prevent the recurrence of a symptomatic neuroma. Materials and Methods This study aims to assess the implantation effects of the NEUROCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 17 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Historically, silicone nerve caps were poorly fitted, allowing axon escape, as well as structurally hard and rigid causing secondary neural irritation and the need for unplanned surgical removal 22 . Neurocap is biotolerant and absorbable so that nerve irritation would be unlikely and, if present, would be transient 13 . This was not found to be an issue in the current study, and the revisions reported were not related to device irritation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Historically, silicone nerve caps were poorly fitted, allowing axon escape, as well as structurally hard and rigid causing secondary neural irritation and the need for unplanned surgical removal 22 . Neurocap is biotolerant and absorbable so that nerve irritation would be unlikely and, if present, would be transient 13 . This was not found to be an issue in the current study, and the revisions reported were not related to device irritation.…”
Section: Discussionmentioning
confidence: 64%
“…Neurocap, a bioresorbable nerve capping device, was developed to reduce symptomatic neuroma formation by isolating and protecting the peripheral nerve end from the surrounding environment. The design specifically limits sprouting and the disorganized axonal swirling observed in a rodent sciatic neuroma model 13 …”
mentioning
confidence: 99%
“…21,22 Commercially available nerve capping devices made of synthetic or biological degradable materials are intended to provide protection from the tissue injury inflammatory environment. 8,9 While these devices can provide a macrostructural template to contain axonal regeneration, they can also create nerve "compartment syndrome" as they can become a "barrier/trap" for growing/sprouting axons. Furthermore, the degradation products of the synthetic material used for one of these technologies (PLLA-PCA) has been associated with a fibrotic inflammatory response, which can further increase the risk of neuroma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available nerve capping devices made of synthetic or biological degradable materials are intended to provide protection from the tissue injury inflammatory environment 8,9 . While these devices can provide a macrostructural template to contain axonal regeneration, they can also create nerve “compartment syndrome” as they can become a “barrier/trap” for growing/sprouting axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation